2018
DOI: 10.3846/16484142.2018.1457568
|View full text |Cite
|
Sign up to set email alerts
|

Co-Solvent Transesterification of Bitter Almond Oil Into Biodiesel: Optimization of Variables and Characterization of Biodiesel

Abstract: Abstract. The influence of co-solvent on transesterification of one of non-edible feedstocks, Bitter Almond Oil (BAO) with methanol was investigated. Hexane and potassium hydroxide (KOH) were chosen as the co-solvent and the catalyst, respectively. The variables included in the optimization process were concentration of KOH, methanol to oil molar ratio, hexane to methanol volume ratio, reaction temperature, reaction time, type of co-solvent and type of the alkali catalyst. BioDiesel (BD) with yield of 97.88 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…Transformation of Hydrilla verticillata , which is an aquatic plant, to BO and charcoal by thermal pyrolysis, was achieved by Promdee et al 16 The literature survey indicated that BO synthesis from the waste seeds and plant seeds still little is compared with other biomass sources. Rapeseeds, 17 Karanja seeds, 18 neem seeds, 19 safflower seeds, 20 castor seeds, 21 jatropha seeds, 22 linseed seeds, 23 cotton seeds, 24 Kaner seeds, 25 pomegranate seeds, 26 sal seeds, 27 cherry seeds, 28 apricot seeds, 29 and date seeds 30 have been utilized as feedstocks for the creation of BO by pyrolysis at various conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transformation of Hydrilla verticillata , which is an aquatic plant, to BO and charcoal by thermal pyrolysis, was achieved by Promdee et al 16 The literature survey indicated that BO synthesis from the waste seeds and plant seeds still little is compared with other biomass sources. Rapeseeds, 17 Karanja seeds, 18 neem seeds, 19 safflower seeds, 20 castor seeds, 21 jatropha seeds, 22 linseed seeds, 23 cotton seeds, 24 Kaner seeds, 25 pomegranate seeds, 26 sal seeds, 27 cherry seeds, 28 apricot seeds, 29 and date seeds 30 have been utilized as feedstocks for the creation of BO by pyrolysis at various conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the sustainability of BD production from edible oils is a chief matter as a consequence of the food versus food crises originates from utilizing these feedstocks 31 . Therefore, the second‐generation BDs were synthesized from different nonedible oils, like Calophyllum inophyllum , Sterculia foetida , Jatropha curcas , and Pongamia pinnata oils, as they have confirmed their suitability as potential substitutes to diesel fuel 30,31 . The second‐generation BDs are also encouraging due to their excellent cold flow properties, high oxidation stability, and low kinematic viscosity.…”
Section: Introductionmentioning
confidence: 99%
“…Almond seed oil has been investigated as a suitable source of biodiesel since it doesn't require the use of antioxidants or cold flow improver to meet biodiesel quality unlike most other vegetable oils (Kumar & Sharma, 2015). Belonging to the Rosacea family, almond is a tree plant which can be found in Africa, Europe, North America and several parts of the Middle East (Fadhil & Mohammed, 2016). Currently, fossil fuel usage accounts for 80% of total energy consumed globally (Suleman et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown little research attention on the effect of blending ratio on the biodiesel potential of vegetable oils. Some of these studies on almond seed oil have focused on the influence of co-solvent on its' yield and quality as well as determination of its' fuel properties (Fadhil & Mohammed, 2016), production and optimization of biodiesel production (Al-Tikrity et al, 2017;Esonye et al, 2018) and its' applications in food, biotechnology and drilling operations (Oseh et al, 2019;Yesiloglu & Baskurt, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Fadhil and Mohammed 2018 [12] examined the biodiesel potential characteristics of non-edible bitter almond oil by co-solvent transesterification with hexane as solvent and potassium hydroxide catalyst (KOH) as alternative fuel to diesel in compression engines. It was reported that the properties of the biodiesel and its blends complied with the limits prescribed by ASTM D7467-17.…”
Section: Introductionmentioning
confidence: 99%